Population size of Aegla longirostri Bond-Buckup and Buckup, 1994 (Crustacea, Decapoda, Anomura): comparison of methods with the mark-recapture technique in closed population - Baumart,Joele S. (2018)
Abstract The aim of this study is to estimate the population size of Aegla longirostri Bond-Buckup and Buckup, 1994 in a subtropical low-order stream using the mark-recapture technique. We also tested if the Bayesian model is a promising estimator of population size. Data were collected in two periods, in spring 2010 (seven-day sampling) and in fall 2011(five-day sampling). The animals were sexed, measured, marked in the field, and released in the same spots from which they were collected. During the study period, 445 adults were captured (343 in the spring and 102 in the fall). The estimated population size was 1,005-1,028.8 individuals in the spring and 234-236 in the fall, according to the Schumacher-Eschmeyer and Schnabel methods, respectively. The estimated population size using the Bayesian analysis was 950.13 individuals in the spring and 210.08 in the fall. Although the Bayesian model is a more conservative approach, all methods showed similar and relevant estimations of population size.